Implementasi Penggunaan Aplikasi Hadirr pada PT. XY - Kusumaningrum, Rachmadita Nurdian; Baskoro, Heru (IAI Nasional Laa Roiba Bogor, 2024)
XYZ, is a company engaged in land transportation, distribution of building materials, production of mining materials, and trading of industrial goods. In the current era of globalization, it brings changes to all aspects of life. The development of information technology encourages people to use technology, one of which is the use of online attendance system technology implemented by PT. XYZ is the “Hadirr” application. This research discusses the implementation of the use of the presence application at PT. XYZ aims to find out how disciplined employees are in taking online attendance. This type of research is descriptive qualitative research, research involving 5 informants through observation, interviews and documentation, this identifies factors such as lack of employee discipline, misuse of applications so that employee discipline that has been implemented by the company is less effective. Employee work discipline can be seen from employee compliance in complying with applicable regulations, including punctuality and responsibility for their work. To overcome this problem, companies can provide rewards as a form of appreciation for work, provide additional intensive work, and provide intensive supervision. These steps can improve the employee discipline process so that the company can achieve the desired goals Keywords: Hadirr Application, Discipline, Employee